Penghantaran Data Melalui Saluran VHF - Mohamad, Noor Shazrah (Universiti Sains Malaysia, 2006)
The scope of this project is the data transmission over VHF link. The main emphasise of this project is to find suitable digital modulation technique for VHF transmission. VHF is the radio frequency ranging from 30MHz to 300MHz. VHF frequencies' propagation characteristics are ideal for short-distance terrestrial communication, with a range generally somewhat farther than line-of-sight from the transmitter. VHF is also less affected by atmospheric noise and interference from electrical equipment than low frequencies. The main objective from this project is to design VHF radio modem. Preliminary study need to be carried out to achieve the project objective. After the study the transmitter, receiver and control circuit would be designed. Control circuit is needed to interface with the voltage divider circuit to get the suitable value as data input for FSK encoder circuit. The clamper circuit is used raise the DC voltage level of the input data logic “0” to 1volt. The circuit was designed using ORCAD software. The circuit was fabricated and tested.